2015
DOI: 10.1042/bj20141373
|View full text |Cite
|
Sign up to set email alerts
|

Conserved proline-directed phosphorylation regulates SR protein conformation and splicing function

Abstract: The alternative splicing of human genes is dependent on SR proteins, a family of essential splicing factors whose name derives from a signature C-terminal domain rich in arginine-serine dipeptide repeats (RS domains). Although the SRPKs (SR-specific protein kinases) phosphorylate these repeats, RS domains also contain prolines with flanking serines that are phosphorylated by a second family of protein kinases known as the CLKs (Cdc2-like kinases). The role of specific serine-proline phosphorylation within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 52 publications
3
73
0
Order By: Relevance
“…So the understanding of molecular mechanisms of ESCC can benefit patients very well. SRPK1, a highly conserved protein in eukaryotic organisms, is comprised of a PKC superfamily kinase domain and a spacer region that divides the kinase domain by half [6,7]. Some reports demonstrate the key role of SRPK1 in phosphorylation of specific amino acids of proteins rich in serinearginine repeats that is called as RS domain proteins [8].…”
Section: Introductionmentioning
confidence: 99%
“…So the understanding of molecular mechanisms of ESCC can benefit patients very well. SRPK1, a highly conserved protein in eukaryotic organisms, is comprised of a PKC superfamily kinase domain and a spacer region that divides the kinase domain by half [6,7]. Some reports demonstrate the key role of SRPK1 in phosphorylation of specific amino acids of proteins rich in serinearginine repeats that is called as RS domain proteins [8].…”
Section: Introductionmentioning
confidence: 99%
“…SR-25, as other SR proteins, is also rich in potential phosphorylation residues and motifs (29). Previous studies demonstrated that a specific conformation of the SR proteins is required for their protein-protein interactions or for their phosphorylation/dephosphorylation during the splicing cycle (32). However, the highly repetitive sequence composition and the presence of multiple proline residues in the SR domains of SR proteins indicate that they are rather unstructured (33).…”
Section: Sr-25 Is Upregulated By Cypa Overexpression In Vitromentioning
confidence: 89%
“…It can be speculated that the PPIase activity may be involved in the interaction between CypA and SR-25. SR proteins are phosphoproteins, and their phosphorylation status can affect their ability to interact with splicing complexes (21,32). SR-25, as other SR proteins, is also rich in potential phosphorylation residues and motifs (29).…”
Section: Sr-25 Is Upregulated By Cypa Overexpression In Vitromentioning
confidence: 99%
“…Although some splice events are known where one splicing factor is the dominant regulator, in many cases alternative splicing is determined by the sum of the activity of several splicing regulatory proteins (15,16). The activity of such proteins can be controlled by changes in expression or by posttranslational modifications that can control localization or RNA binding capability for example (17)(18)(19)(20)(21). Altered activity may then result in alternative splicing of several or many exons in a concerted manner, thus contributing to establish global splicing patterns, for example in a tissue-specific manner (9,(22)(23)(24)(25).…”
mentioning
confidence: 99%